Acetyl CoA Carboxylase: Isolation and Characterization of Native Biotin Carboxyl Carrier Protein - Fall, R. Ray (1971)
A large form of biotin carboxyl carrier protein (BCCP(L)) has been isolated from extracts of Escherichia coli. It has a minimal molecular weight of 20,000, according to its behavior on sodium dodecylsulfate-polyacrylamide gel electrophoresis, and contains approximately 1 mol of biotin per 22,000 g of protein. BCCP(L) exhibits K(m) values, in the biotin carboxylase and transcarboxylase half-reactions of acetyl CoA carboxylase, of 2 × 10(-7) M and 4 × 10(-7) M, respectively; these values are 50-100 times lower than those obtained with smaller forms of BCCP previously isolated. Electrophoresis of crude extracts of E. coli indicates that the major biotin-containing protein migrates at the same rate as BCCP(L), which suggests that BCCP(L) is the native form of BCCP in E. coli.